The prophet - Gibran, Kahlil, 1883-1931 (Wilco, 2018)
Kahlil Gibran offers dogma-free universal spiritualiam as opposed to orthodox religion - and the poet's vision of spirituality is far from being moralistic. In fact, he urges people to be non-judgmental. The lines from this perennial classic have inspired global luminaries, song lyrics and political speech writers. It has a way of speaking to people at different stages in their own lives; the more you read it the more you enjoy and relish the words.